Fishermen Community Based Tourism Development in Packaging Surf Fishing Activities for Tourist in Pangandaran Beach Destination - Beta Budisetyorini; Deddy Adisudharma; Dicky Arsyul Salam; Wisi Wulandari; Mega Fitriani Adiwarna Prawira (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2022)
The coastal area in Pangandaran Beach Destination has been developed for marine tourism activities. Surf fishing by Cikidang village fisherman is one of marine activities that attract tourists for recreation. Surf fishing is one of sustainable fishing techniques for marine tourism development which provide Cikidang fishermen opportunity to create it as tourist fishing activities in friendly environment. This community service study aims to investigate the challenge and benefit, also assist the Cikidang fisherman community in making surf fishing tourism package as community based tourism development to increase their additional income as well as to enhance their surf fishing tourism product development knowledge and skill. The method used in this community service study is a participatory survey approach and analyzed descriptively based on depth-interview and field observation. The result of this study show the surf fishing is a friendly environment activities. The surf fishing tourism package program operation phase should be divided into three stages consist of preparation, catching, and cooking services for one day tourist activities. The surf fishing operator is suggested managed by three type of fishermen group associated with the Cikidang fish auction place. The offering surf fishing tourism package price is calculated based on the fisherman local guide fee, surf fishing tools and equipment rate, and cooking services rate.